2016
DOI: 10.1371/journal.pone.0148447
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Genetic Structure of the Abundant and Widespread Peatmoss Sphagnum magellanicum Brid.

Abstract: Spore-producing organisms have small dispersal units enabling them to become widespread across continents. However, barriers to gene flow and cryptic speciation may exist. The common, haploid peatmoss Sphagnum magellanicum occurs in both the Northern and Southern hemisphere, and is commonly used as a model in studies of peatland ecology and peatmoss physiology. Even though it will likely act as a rich source in functional genomics studies in years to come, surprisingly little is known about levels of genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 70 publications
1
34
0
6
Order By: Relevance
“…However, S. magellanicum is a species with a very broad niche and found in a range of habitats with varying degrees of groundwater influence (Flatberg 2013). These species are easy to identify but recent research has shown that the dark European morph of S. fuscum is conspecific to the North American S. beothuk (Kyrkjeeide et al 2015), and S. magellanicum has been shown to consist of two genetically diverged morphotypes (Kyrkjeeide et al 2016). Unpublished genetic data suggest that samples collected in our study consist of both S. magellanicum morphs (approximately 50/50) and possibly one or two samples of S. beothuk (Pers.…”
Section: Study Species and Collection Sitesmentioning
confidence: 60%
“…However, S. magellanicum is a species with a very broad niche and found in a range of habitats with varying degrees of groundwater influence (Flatberg 2013). These species are easy to identify but recent research has shown that the dark European morph of S. fuscum is conspecific to the North American S. beothuk (Kyrkjeeide et al 2015), and S. magellanicum has been shown to consist of two genetically diverged morphotypes (Kyrkjeeide et al 2016). Unpublished genetic data suggest that samples collected in our study consist of both S. magellanicum morphs (approximately 50/50) and possibly one or two samples of S. beothuk (Pers.…”
Section: Study Species and Collection Sitesmentioning
confidence: 60%
“…While this too could be a habitat effect, it has recently been suggested that mire margin populations of S. magellanicum may differ genetically (perhaps even taxonomically) from bog populations (Kyrkjeeide et al. ). Open, ombrotrophic bog is the main habitat of S. fuscum , and the low decay in bog compared to fen is compatible with this.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption may be violated in a few cases, but in general, even species with intercontinental ranges appear to conform to the monophyly assumption and indeed, genetic divergence among plants growing on separate continents is often minimal, even though some geographically correlated genetic structure is the rule rather than the exception (e.g., Kyrkjeeide, Hassel, Flatberg, Shaw, Brochmann, et al, 2016;Kyrkjeeide, Hassel, Flatberg, Shaw, Yousefi, et al, 2016;Shaw et al, 2014;Shaw, Shaw, Johnson, Devos, & Carter, 2015;Stenøien, Shaw, Shaw, Hassel, & Gunnarsson, 2011;Szövényi, Terracciano, Ricca, Giordano, & Shaw, 2008). This assumption may be violated in a few cases, but in general, even species with intercontinental ranges appear to conform to the monophyly assumption and indeed, genetic divergence among plants growing on separate continents is often minimal, even though some geographically correlated genetic structure is the rule rather than the exception (e.g., Kyrkjeeide, Hassel, Flatberg, Shaw, Brochmann, et al, 2016;Kyrkjeeide, Hassel, Flatberg, Shaw, Yousefi, et al, 2016;Shaw et al, 2014;Shaw, Shaw, Johnson, Devos, & Carter, 2015;Stenøien, Shaw, Shaw, Hassel, & Gunnarsson, 2011;Szövényi, Terracciano, Ricca, Giordano, & Shaw, 2008).…”
mentioning
confidence: 99%